Temporal and spatial analysis and monitoring of drought (meteorology) and its impacts on environment changes in Iran. (17th February 2022) - Safarianzengir, Vahid; Fatahi, Ahmad; Sobhani, Behrouz; Doumari, Sahar Amiri
Abstract: The consequences of climate change, primarily due to natural and human factors, have caused many problems in the last decade that have affected different sections of society. One of the most important consequences is the occurrence of natural atmospheric—climatic disasters (drought). One of these regions is Iran in the Middle East, which has been suffering from this drought in the last decade. This investigation aims to evaluate and monitor drought and its impacts on environment changes in Iran. To conduct this research, the TERRA satellite data and the MODIS sensor were used over a 21‐year period, and the Normalised Differential Vegetation Index and Palmer Drought Severity Index Indicators were used to monitor drought and to estimate the soil moisture by the Soil Moisture Calculation satellite. Finally, to estimate the amount of precipitation and evapotranspiration, cumulative precipitation and real evapotranspiration, actual evaporation and transpiration were used. Findings showed that in the investigation region, the severity and frequency of drought have increased in recent years. Soil moisture has also decreased, indicating the inverse relationship between drought intensity and soil surface moisture, meaning that as the intensity of drought increases, the amount of soil surface moisture decreases. However, in the investigation region during the study course, the accumulation of rain showed a direct relationship with evaporation and transpiration. The highest monthly drought intensity of Palmer was 5.65% in May 2000. Also, the highest amount of wet year in November 2018 is 3.6%. The highest amount of rainfall was 61.25 mm in October 2018. Based on the results obtained in this research, drought has occurred in the investigation region in recent years, the intensity of which in the south, eastern and centre half of the country, especially the provinces of south Khorasan, Semnan, Hormozgan, Sistan and Baluchestan, Khuzestan and Ilam more it has been more than other provinces. To manage and control drought in the investigation region, in the various sectors affected by drought (agriculture, environment, surface water resources, forests, pastures and watershed management and natural ecosystems) strategies and plans in the short term, medium‐term and long‐term in line with natural and human factors and climate change to be adopted. Abstract : Study of different processes and stages.